2018
DOI: 10.1098/rsos.180577
|View full text |Cite
|
Sign up to set email alerts
|

Structural and temporal patterns of the first global trading market

Abstract: Little is known about the structural patterns and dynamics of the first global trading market (FGTM), which emerged during the sixteenth century as a result of the Iberian expansion, let alone how it compares to today's global financial markets. Here we build a representative network of the FGTM using information contained in 8725 (handwritten) Bills of Exchange from that time—which were (human) interpreted and digitalized into an online database. We show that the resulting temporal network exhibits a hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Western popular music markets present power law distributions in the lifetime of albums [50]. Stock markets exhibited power law distributions since their very beginning [51]. It has been shown that the number of trades per day, the size of price movements when a large volume of shares are bought or sold, and the number of shares traded per time period are power law distributed with exponents 3, 0.5 and 1.5, respectively [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Western popular music markets present power law distributions in the lifetime of albums [50]. Stock markets exhibited power law distributions since their very beginning [51]. It has been shown that the number of trades per day, the size of price movements when a large volume of shares are bought or sold, and the number of shares traded per time period are power law distributed with exponents 3, 0.5 and 1.5, respectively [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Western popular music markets present power law distributions in the lifetime of albums [44]. Stock markets exhibited power law distributions since their very beginning [45]. It has been shown that the number of trades per day, the size of price movements when a large volume of shares are bought or sold, and the number of shares traded per time period are power law distributed with exponents 3, 0.5 and 1.5, respectively [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, such system develops relevant norms and institutions to protect them, in the first place, such as the securities market. Then there is the shift of the priority of legislation and other institutions from delegating only the right to possess the means of concomitant production to the delegation of right of use when the owners only financially involved into the enterprise, rarely making significant decisions about it [26][27][28]. Herewith, maritime trading was among the first industries made this transition, switching to the delegation of the right of use by ship owners.…”
Section: Ownershipmentioning
confidence: 99%